DEEP - a new publication on development - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
DEEP, World Campaign Against Hunger, Action Development, FAO, Via delle Terme di Caracalla, 00100 Rome, ITALY